The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.15624
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional regulation of stemness gene Lgr5 in esophageal squamous cell carcinoma

Abstract: Cancer stem cells (CSCs) are defined as a rare subpopulation of undifferentiated cells with biological characteristics that include the capacity for self-renewal, differentiation into various lineages, and tumor initiation. To explore the mechanism of CSCs in esophageal squamous cell carcinoma (ESCC), we focused on Leucine-rich repeat containing G protein-coupled receptor 5 (Lgr5), a target gene of the Wnt signaling pathway, which has been identified as a marker of intestinal stem cells and shown to be overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…As previously reported, LGR5 can promote the invasion and migration of colorectal cancer ( 16 ), esophageal squamous cell carcinoma ( 20 ) and gastric cancer ( 21 ). To further confirm the role of LGR5 in NSCLC cell migration, we performed a wound-healing assay with LGR5-transfected and Mock-transfected NSCLC cells.…”
Section: Resultssupporting
confidence: 55%
“…As previously reported, LGR5 can promote the invasion and migration of colorectal cancer ( 16 ), esophageal squamous cell carcinoma ( 20 ) and gastric cancer ( 21 ). To further confirm the role of LGR5 in NSCLC cell migration, we performed a wound-healing assay with LGR5-transfected and Mock-transfected NSCLC cells.…”
Section: Resultssupporting
confidence: 55%
“…Reports have shown that the CSC marker, EpCAM, may be successfully used as a tumor marker in gastric, ovarian, and breast cancer because its high expression in these cancers is closely related to tumor growth, metastasis and advanced tumor stage (30)(31)(32). Similarly, increased expression of LGR5 in esophageal cancer and neuroblastoma can enhance tumor cell invasion and migration (33,34). Moreover, studies are underway to determine the relationship between LGR5 and PTC (35).…”
Section: Discussionmentioning
confidence: 99%
“…161 Lgr5, a member of the G proteincoupled receptor (GPCR) family of proteins, is located downstream of the Wnt signaling pathway and restrains the differentiation of esophageal SCC stem cells. 162 Wnt signaling also plays an important role in regulating CSC apoptosis. Dickkopf-related protein 2 induces G0/G1 arrest and cell apoptosis by suppressing β-catenin activity in breast CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%